Generation of High-Affinity Chicken Single-Chain Fv Antibody Fragments for Measurement of the Pseudonitzschia pungens Toxin Domoic Acid - Finlay, William J. J. (American Society for Microbiology, 2006)
Antibody-based assay systems are now accepted by regulatory authorities for detection of the toxins produced by phytoplankton that accumulate in shellfish tissues. However, the generation of suitable antibodies for sensitive assay development remains a major challenge. We have examined the potential of using the chicken immune system to generate high-affinity, high-specificity recombinant antibody fragments against phytotoxins. Following immunization of the chicken with domoic acid-bovine serum albumin, a single-chain antibody variable region (scFv) gene library was generated from single V(H) and V(L) genes isolated from the immune cells in the spleen and bone marrow. scFvs reacting with domoic acid were isolated by phage display and affinity matured by light chain shuffling, resulting in an approximate 10-fold increase in sensitivity. The isolated scFvs were effectively expressed in Escherichia coli and readily purified by affinity chromatography. They were then used to develop a convenient and sensitive indirect competitive enzyme-linked immunosorbent assay for domoic acid, with a 50% effective dose of 156 ng/ml, which could be used reliably with shellfish extracts. This study demonstrates that chickens provide a valuable model system for the simplified, rapid generation of high-affinity recombinant antibody fragments with specificity for small toxin molecules.